AA. VV., Code of Canon Law annotated latin-english edition of the Code of Canon Law and English language translation of the 5th Spanish-language edition of the comentary prepared under the responsibility of the Instituto Martin de Azpilcueta: [Rezension] - La Terra, Paolo (Apollinaris, 1995)
Ergänzung zum Titel: hrsg. von Caparro-M., E.; Thorn, Theriault-J., Montreal 1993. Erläuterungen zum kommentierten Codex (lat.-engl.)